2023
DOI: 10.3934/nhm.2023051
|View full text |Cite
|
Sign up to set email alerts
|

A PDE-ODE model for traffic control with autonomous vehicles

Abstract: <abstract><p>We consider a partial differential equation - ordinary differential equation system to describe the dynamics of traffic flow with autonomous vehicles. In the model, the bulk flow of human drivers is represented by a scalar conservation law, while each autonomous vehicle is described by an ordinary differential equation. The coupled PDE-ODE model is introduced, and existence of solutions for this model is shown, along with a proposed algorithm to construct approximate solutions. Next, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In the introduction of this chapter, we indicated that the analysis of coupled systems of ODEs and hyperbolic PDEs can be motivated by so-called motion-planning problems; see e. g. [36,37,45,68,96]. Other fields of application include problems in traffic control [79] or the piston problem [19,20]. In these articles, the coupled systems take the form of a cascading system, i. e. the ODE and the PDE part of the system are usually coupled only at one part of the boundary.…”
Section: Relation To Other Coupled Systems and Hyperbolic Systemsmentioning
confidence: 99%
“…In the introduction of this chapter, we indicated that the analysis of coupled systems of ODEs and hyperbolic PDEs can be motivated by so-called motion-planning problems; see e. g. [36,37,45,68,96]. Other fields of application include problems in traffic control [79] or the piston problem [19,20]. In these articles, the coupled systems take the form of a cascading system, i. e. the ODE and the PDE part of the system are usually coupled only at one part of the boundary.…”
Section: Relation To Other Coupled Systems and Hyperbolic Systemsmentioning
confidence: 99%